The Usefulness of Social Network Analysis in School Bullying Research - Tłuściak-Deliowska, Aleksandra (INSTED: Interdisciplinary Studies in Education & Society, 2014)
The article presents social network analysis as a research method and its practical applicability in the study of bullying in school. This method allows for reconstruction and multi-dimensional analysis of dynamic social networks, which is crucial for the analyzed phenomenon. Researchers dealing with the issues of aggressive behaviour have recently made a particular use of the network concept, its tools and methods. The research based on this analysis can be considered as a starting point to take steps to examine, then reduce and prevent bullying in schools.